A Case of Rheumatoid Arthritis and Limited Systemic Sclerosis Overlap Successfully Treated with Tocilizumab for Arthritis and Concomitant Generalized Lymphadenopathy and Primary Biliary Cirrhosis - Eiko Saito; Shinji Sato; Shinichi Nogi; Noriko Sasaki; Naofumi Chinen; Kiri Honda; Takayuki Wakabayashi; Chiho Yamada; Naoya Nakamura; Yasuo Suzuki (Case Reports in Rheumatology)
A 57-year-old woman with rheumatoid arthritis (RA) and limited systemic sclerosis (lSSc) was suspected to have lymphadenopathy and primary biliary cirrhosis (PBC). Lymph node biopsy showed reactive follicular lymphadenopathy with intrafollicular plasmacyte infiltration that was interleukin-6 positive by immunohistostaining. Because of gradually worsening arthritis, tocilizumab was administered and arthritis improved markedly. Interestingly, lymphadenopathy and PBC improved simultaneously. This suggested that interleukin-6 might play an important role in reactive lymphadenopathy and PBC associated with RA/lSSc.